Effectiveness of kojame (red ginger compress) on chest pain and anxiety in patients with acute coronary syndrome - Saputri, Niken Anggraini Sri; Ta'adi, Ta'adi; Suharsono, Suharsono (Media Keperawatan Indonesia, 2024)
Acute coronary syndrome can cause chest pain with a heavy quality, radiating to the left arm, neck, jaw and back. Uncontrolled chest pain will cause physiological and psychological problems in the form of anxiety, and abnormal heartbeat. This problem can be treated with non-pharmacological intervention in the form of a red ginger compress which can increase capillary permeability, histamine release and vasodilation, thereby relaxing muscle and nerve tissue in acute coronary syndrome patients. The research aims to explain the effectiveness of giving kojame (compressing red ginger) to chest pain and anxiety in patients with acute coronary syndrome. The research design uses a Quasi Experiment study with Pre-Post Test with Control Group Design. The sample size was 57 respondents with each group consisting of 19 respondents, using a consecutive sampling technique. The intervention for each group was given 4 times for 20-30 minutes in 2 days. Analysis of this research data used the Wilcoxon test and Mann-Whitney test (ρ<0.05). Shows from the two groups the kojame intervention (red ginger compresses) is more influenced by a decrease in chest pain and anxiety with a value of ρ-value 0.008. Kojame intervention (red ginger compress) is more effective in reducing chest pain and anxiety in patients with acute coronary syndrome.